Penegakan Hukum Pidana Lingkungan Dalam Perlindungan Hak Asasi Manusia di Bidang Lingkungan Hidup - Fatich Nurhadi (Yuriska: Jurnal Ilmiah Hukum, 2023)
Background: The high number of coal industries in Samarinda City has triggered various environmental pollution issues. This occurs due to the many negligence of the coal industry players in carrying out reclamation efforts which then have an impact on the welfare of the community in the area around the mining area. This form of neglect is a form of violation of human rights, namely the right to have a clean and healthy environment, and law enforcement should be enforced to create a deterrent effect. The government of Samarinda City has played a role at various levels in ensuring the fulfillment of human rights related to the environment. Research Method: This research uses juridical sociological and psychological juridical methods. The research approach uses a statutory regulatory approach, namely Law No. 32 of 2009 concerning Protection and Management of the Environment, Law No. 4 of 2009 concerning Mineral and Coal Mining, Law No. 8 of 1981 concerning the Law Code. Criminal Procedure Law, as well as Law No. 39/1999 on Human Rights. Findings: The analysis shows that the government plays an important role in ensuring the fulfillment of human rights related to the environment. Conclusion: The Samarinda City Government strictly carries out regulations regarding the implementation of mining businesses, especially those related to reclamation, in accordance with Law Number 4 of 2009 concerning Mineral and Coal Mining.